The Impact of Bispectral Index Monitoring on Outcomes in Spinal Cord Stimulation for Chronic Disorders of Consciousness - Chen X; Qin X; Zhuang Y; Li Z; Liang Z; Zhang H; Yao L; Li X; He J; Guo X (Dove Medical Press, 2024)
Xuanling Chen,1,* Xuewei Qin,1,* Yutong Zhuang,2 Zhengqian Li,3 Zhenhu Liang,4 Hua Zhang,5 Lan Yao,1 Xiaoli Li,6 Jianghong He,7 Xiangyang Guo3 1Department of Anesthesiology, Peking University International Hospital, Beijing, People's Republic of China; 2Department of Neurosurgery, The Second School of Clinical Medicine, Southern Medical University, Guangzhou, Guangdong, People's Republic of China; 3Department of Anesthesiology, Peking University Third Hospital, Beijing, People's Republic of China; 4Institute of Electrical Engineering, Yanshan University, Qinhuangdao, People's Republic of China; 5Clinical Epidemiology Research Center, Peking University Third Hospital, Beijing, People's Republic of China; 6The State Key Laboratory of Cognitive Neuroscience and Learning & IDG/McGovern Institute for Brain Research, Beijing Normal University, Beijing, People's Republic of China; 7Department of Neurosurgery, Tiantan Hospital, Capital Medical University, Beijing, People's Republic of China*These authors contributed equally to this workCorrespondence: Xiangyang Guo, Peking University, Third Hospital, 49 huayuan North Road, Haidian District, Beijing, 100191, People's Republic of China, Email puthmzk@hsc.pku.edu.cn Jianghong He, Beijing Tiantan Hospital, 119 South Fourth Ring Road West, Fengtai District, Beijing, 100069, People's Republic of China, Email hejianghong@sina.cnObjective: To observe whether maintaining the appropriate depth of anesthesia with Bispectral Index (BIS) can improve the prognosis of Spinal Cord stimulation (SCS) implantation in patients with chronic Disorders of consciousness (DoC).Methods: 103 patients with DoC undergoing SCS implantation were reviewed, and 83 patients with DoC were included according to the standard of inclusion and exclusion Criteria. Patients were divided into a BIS group (n =45) and a non-BIS group (n =38) according to whether BIS monitoring was used during the operation. The depth of anesthesia in the BIS group was maintained between 40- 60. The anesthesiologist adjusted the depth of anesthesia in the non-BIS group according to clinical experience. Relevant information such as disease course, cause, anesthesia time, and operation time were collected. Preoperative CRS-R(preoperative) score, postoperative CRS-R(24h), and postoperative CRS-R(3m) changes were collected.Results: The CRS-R(3m) score in the BIS group was higher than that in the non-BIS group (preoperative), and the difference was statistically significant (P < 0.05). In CRS-R (24h), the BIS group was higher than the non-BIS group, and the difference was statistically significant (X2=8.787, P =0.004). The improvement of consciousness was included in the multivariate Logistic regression analysis model, and it was found that the thalamus was an independent factor affecting the improvement of consciousness (P < 0.05). During follow-up, 1 patient in the BIS group had a decrease in consciousness from MCS− to VS/ UWS and 2 patients in the non-BIS group died during follow-up.Conclusion: Patients can be benefit in hearing in CRS-R (24h). We recommend the use of BIS to monitor the depth of anesthesia in patients with DoC to improve patient outcomes.Keywords: chronic disturbance of consciousness, vegetative state/unresponsive wakefulness syndrome, spinal cord stimulation, general anesthesia, bispectral index, improved coma recovery scale